2015
DOI: 10.1007/s13277-015-3423-1
|View full text |Cite
|
Sign up to set email alerts
|

The high expression of TC1 (C8orf4) was correlated with the expression of β-catenin and cyclin D1 and the progression of squamous cell carcinomas of the tongue

Abstract: Thyroid cancer 1 (TC1, C8orf4) plays important roles in many signaling pathways, such as Wnt/β-catenin signaling pathway, and is involved in the development of many cancers. The objective of this study was to examine the expression of TC1 and investigate the associations among TC1, β-catenin, Chibby, cyclin D1, and the clinicopathological factors of oral tongue squamous cell carcinomas (OTSCCs). The expressions of TC1, β-catenin, Chibby, and cyclin D1 were examined in 109 cases of OTSCCs using immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…For example, Chromosome 8 Open Reading Frame 4 (C8orf4), ranked 9th by NMF, was identified as “ Thyroid cancer 1 (TC1)” (Panebianco et al, 2015; Zhang et al, 2015; Zhu et al, 2015; Huang et al, 2016). Epidermal Growth Factor Receptor (EGFR), a gene ranked 31st by NMF, has elevated expression from MGH29 to MGH31.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Chromosome 8 Open Reading Frame 4 (C8orf4), ranked 9th by NMF, was identified as “ Thyroid cancer 1 (TC1)” (Panebianco et al, 2015; Zhang et al, 2015; Zhu et al, 2015; Huang et al, 2016). Epidermal Growth Factor Receptor (EGFR), a gene ranked 31st by NMF, has elevated expression from MGH29 to MGH31.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported high expression levels of TC1 across a wide range of tumors, and a positive association with malignancy [ 10 , 13 , 17 19 , 23 , 24 ]. However, reduced expression of TC1 was observed in colon cancer tumors relative to normal mucosa [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that TC1 promotes tumor development primarily by enhancing the activity of the Wnt/β-catenin signaling pathway [ 10 , 13 , 19 , 23 ]. However, the relationship between TC1 and other key members of the Wnt/β-catenin signaling pathway is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 299 gastric cancers, TC-1 expression was in correlation with a subset of β-catenin target genes, including laminin γ2, metalloproteinase-7 and metalloproteinase-14, cyclin D1, c-Met, and CD44 ( Kim et al, 2006a ). High expression of TC-1 was common in 109 cases of oral tongue squamous cell carcinomas (OTSCCs) and correlated with the expression of β-catenin and cyclin D1, indicating the carcinogenesis of TC-1 in OTSCCs by enhancing the activity of Wnt/β-catenin signaling pathway ( Zhang et al, 2015 ). TC-1 was also observed in 97 of the 147 primary tumor specimens of NSCLC, and it was correlated with the TNM stage as well as regional lymph node metastasis, which was in line with the results of in vitro experiments demonstrating that it promoted the proliferation and invasion of lung cancer cells through Wnt/β-catenin signaling pathway ( Su et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%